Espaços Protegidos Transfronteiriços:: Patrimônio Natural e Territórios na Bacia do Alto Paraguai (Sustainability in Debate, 2011)
The goal of this paper is to analyse the concept of natural heritage in transboundaryspaces. After introducing the concept of natural heritage, we discuss its implicationin the Paraguay watershed. In fact there is a clash between natural and politicalspatial unities. We argue that patrimonialisation/territorialisation provide a newinstitutional framework to the south America regional integration.